An integrated metabolome and transcriptome approach reveals the fruit flavor and regulatory network during jujube fruit development - Lu, Dongye; Zhang, Lei; Wu, Yang; Pan, Qinghua; Zhang, Yuping; Liu, Ping (Frontiers in Plant Science, 2022)
The fruit flavor is a key economic value attribute of jujube. Here we compared metabolomes and transcriptomes of ‘Mazao’ (ST) and ‘Ping’anhuluzao’ (HK) with unique flavors during fruit development. We identified 437 differential metabolites, mainly sugar, acid, and lipid. Fructose, glucose, mannose and citric acid, and malic acid are the determinants of sugar and acid taste of jujube fruit. Based on the transcriptome, 16,245 differentially expressed genes (DEGs) were identified, which were involved in “glucosyltransferase activity”, “lipid binding”, and “anion transmembrane transporter activity” processes. Both transcriptome and metabolome showed that stages 2 and 3 were important transition periods for jujube maturation. Based on WGCNA and gene-metabolite correlation analysis, modules and transcription factors (ZjHAP3, ZjTCP14, and ZjMYB78) highly related to sugar and acid were identified. Our results provide new insights into the mechanism of sugar and acid accumulation in jujube fruit and provide clues for the development of jujube with a unique flavor.